Efficacy and safety of dulaglutide monotherapy compared with glimepiride in East‐Asian patients with type 2 diabetes in a multicentre, double‐blind, randomized, parallel‐arm, active comparator, phase III trial. Issue 9 (5th June 2018) - Chen, Yu Hong; Huang, Chien‐Ning; Cho, Young Min; Li, Pengfei; Gu, Liqun; Wang, Feng; Yang, Jun; Wang, Wei Qing
Abstract : Aims: To compare the efficacy and safety of once‐weekly glucagon‐like peptide‐1 receptor agonist dulaglutide 1.5 and 0.75 mg with glimepiride in East‐Asian patients with type 2 diabetes (T2D). Materials and methods: In this phase III, multinational, multicentre, double‐blind, randomized, parallel‐arm, 26‐week study, patients with inadequate glycaemic control were randomized 1:1:1 to once‐weekly dulaglutide 1.5 or 0.75 mg or daily glimepiride (1‐3 mg/d). The primary endpoint was assessment of the non‐inferiority of dulaglutide (1.5 mg), as measured by change in glycated haemoglobin (HbA1c), compared with glimepiride using a 0.4% non‐inferiority margin. Results: A total of 737 patients were randomized (dulaglutide 1.5 mg, n = 244; dulaglutide 0.75 mg, n = 248; glimepiride, n = 245). At week 26, both doses of dulaglutide were non‐inferior and also superior to glimepiride for HbA1c reduction from baseline with a least squares mean difference of −6.34 mmol/mol (95% confidence interval [CI] −8.31, −4.26) or ‐0.58% (95% CI −0.76, −0.39) for dulaglutide 1.5 mg and −3.50 mmol/mol (95% CI −5.47, −1.42) or −0.32% (95% CI −0.50, −0.13) for dulaglutide 0.75 mg ( P < .001). A greater proportion of patients in the dulaglutide 1.5 mg group achieved the HbA1c target of <53 mmol/mol (<7.0%) compared with the glimepiride group (74.1% vs 57.4%; P < .001). The mean body weight decreased ( P < .005) and total hypoglycaemia rates were lower ( P < .001) in the dulaglutide groups compared with the glimepiride group. The most common drug‐related adverse events in both dulaglutide groups (≥5% of patients) included diarrhoea, nausea, increased lipase, decreased appetite, abdominal distension and vomiting. Conclusions: Dulaglutide (both doses) demonstrated superior glycaemic control vs glimepiride, with a favourable tolerability and safety profile in East‐Asian patients with T2D.